2017
DOI: 10.1002/jmv.24798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genome sequences and clinical features of coxsackievirus A6 strains collected in Hyogo, Japan in 1999‐2013

Abstract: Coxsackievirus A6 (CV-A6) is an enterovirus, which is known to cause herpangina. However, since 2009 it has frequently been isolated from children with hand, foot, and mouth disease (HFMD). In Japan, CV-A6 has been linked to HFMD outbreaks in 2011 and 2013. In this study, the full-length genome sequencing of CV-A6 strains were analyzed to identify the association with clinical manifestations. Five thousand six hundred and twelve children with suspected enterovirus infection (0-17 years old) between 1999 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
(57 reference statements)
0
15
1
Order By: Relevance
“…Phylogenetic analysis revealed that the majority of circulating CV‐A6 strains detected from 2011 to 2015 in Osaka City and CV‐A6 strains detected from 1999 to 2009 in Japan classified into different clades. Another report describes a similar trend, and so the clade to which an infecting virus belongs to might be a one of the determinants as to whether HFMD or herpangina occurs . In cases of EV‐A71, it is reported that amino acid substitutions in VP1 are responsible for increased virulence, adaptation to the host, and tissue dissemination .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Phylogenetic analysis revealed that the majority of circulating CV‐A6 strains detected from 2011 to 2015 in Osaka City and CV‐A6 strains detected from 1999 to 2009 in Japan classified into different clades. Another report describes a similar trend, and so the clade to which an infecting virus belongs to might be a one of the determinants as to whether HFMD or herpangina occurs . In cases of EV‐A71, it is reported that amino acid substitutions in VP1 are responsible for increased virulence, adaptation to the host, and tissue dissemination .…”
Section: Discussionmentioning
confidence: 87%
“…Another report describes a similar trend, and so the clade to which an infecting virus belongs to might be a one of the determinants as to whether HFMD or herpangina occurs. 32 In cases of EV-A71, it is reported that amino acid substitutions in VP1 are responsible for increased virulence, adaptation to the host, and tissue 33,34 However, it is likely that changes in other region may be involved in determining pathogenicity, because only the VP1 region was analysed in this study.…”
Section: Discussionmentioning
confidence: 90%
“…53 A study of severe HFMD cases showed that EV-A71 was the dominant pathogen (79.3%, 2783/3510). 55 CV-A6 usually caused mild HFMD, whose common symptom is some form of generalized (whole-body) rash, 56,57 but it was the most prevalent genotype of other EVs (42.9%, 21/49). 55 In order to study the severity of CV-A6, 57 articles describing severe CV-A6 HFMD patients were included in the meta-analysis.…”
Section: The Rate Of Severe Hfmd Patientsmentioning
confidence: 99%
“…Enterovirus A71 (EV-A71) and coxsackievirus A16 (CV-A16) have been regarded as the major causes of HFMD ( 3 ). CV-A6 was isolated in the United States in 1949 ( 4 ) and has steadily become one of the main viruses causing HFMD outbreaks in Europe, America, and Asia, including China, Japan, Taiwan, and Thailand ( 3 , 5 10 ). Unlike EV-A71, for which the (sub)genogroup designation has been well established ( 11 ), but similar to other coxsackieviruses (CV-A16 and CV-A10), CV-A6 is arbitrarily divided into several phylogenetic clusters or lineages, from cluster A to F ( 12 ) or lineage A to E (E1 and E2) ( 3 ).…”
mentioning
confidence: 99%